Urban entrepreneurialism and sustainable development: a comparative analysis of Chinese eco-developments - Xie, Linjun; Cheshmehzangi, Ali; Tan-Mullins, May; Flynn, Andrew; Heath, Tim (Taylor & Francis, 2019)
Focusing upon the strategic entrepreneurial planning of local government, this paper presents a critical analysis of the variability of Chinese urban sustainable development projects. In recent years, state entrepreneurialism and notions of (urban) sustainability have become ever more closely intertwined. As a result, there has been a proliferation of eco-/low-carbon and other similar sustainability-themed urban initiatives that have helped local states to achieve a favorable position in city competitions. Nevertheless, existing studies are still far from answering why Chinese urban sustainable projects are planned and implemented with divergent emphases and different development trajectories. Through case studies of three flagship Chinese sustainable projects with distinct development modes, namely the real-estate-centric Sino-Singapore Tianjin Eco-City (SSTEC), the environmental-construction-led Chongming Eco-Islands (CEIs), and the industrial development-focused Shenzhen International Low Carbon City (ILCC), we argue that the formulation and implementation of urban sustainable developments are subject to local particularities and different extra-local (mainly municipal and district-level) political-economic contexts. We highlight how both vertical administrative governance and horizontal coordination between territorial jurisdictions underlie the Chinese entrepreneurial planning system, which results in different types of urban entrepreneurships: 1) scalable startup urban entrepreneurship (SSTEC); 2) asset-replacement-urban entrepreneurship (CEIs); and 3) expansion urban entrepreneurship (ILCC). This study also reveals that all three cases experience a development paradox as they strive to reconcile mutually competing economic and environmental imperatives.